Anti-TGFβ (Transforming Growth Factor β) Therapy With Betaglycan-Derived P144 Peptide Gene Delivery Prevents the Formation of Aortic Aneurysm in a Mouse Model of Marfan Syndrome. Issue 9 (September 2021) - Arce, Cristina; Rodríguez-Rovira, Isaac; De Rycke, Karo; Durán, Karina; Campuzano, Victoria; Fabregat, Isabel; Jiménez-Altayó, Francesc; Berraondo, Pedro; Egea, Gustavo
Abstract : Objective: We investigated the effect of a potent TGFβ (transforming growth factor β) inhibitor peptide (P144) from the betaglycan/TGFβ receptor III on aortic aneurysm development in a Marfan syndrome mouse model. Approach and Results: We used a chimeric gene encoding the P144 peptide linked to apolipoprotein A-I via a flexible linker expressed by a hepatotropic adeno-associated vector. Two experimental approaches were performed: (1) a preventive treatment where the vector was injected before the onset of the aortic aneurysm (aged 4 weeks) and followed-up for 4 and 20 weeks and (2) a palliative treatment where the vector was injected once the aneurysm was formed (8 weeks old) and followed-up for 16 weeks. We evaluated the aortic root diameter by echocardiography, the aortic wall architecture and TGFβ signaling downstream effector expression of pSMAD2 and pERK1/2 by immunohistomorphometry, and Tgfβ1 and Tgfβ2 mRNA expression levels by real-time polymerase chain reaction. Marfan syndrome mice subjected to the preventive approach showed no aortic dilation in contrast to untreated Marfan syndrome mice, which at the same end point age already presented the aneurysm. In contrast, the palliative treatment with P144 did not halt aneurysm progression. In all cases, P144 improved elastic fiber morphology and normalized pERK1/2-mediated TGFβ signaling. Unlike the palliative treatment, the preventive treatment reduced Tgfβ1 and Tgfβ2 mRNA levels. Conclusions: P144 prevents the onset of aortic aneurysm but not its progression. Results indicate the importance of reducing the excess of active TGFβ signaling during the early stages of aortic disease progression. Abstract : Supplemental Digital Content is available in the text.